2014
DOI: 10.1007/s00405-014-3288-8
|View full text |Cite
|
Sign up to set email alerts
|

Intratympanic steroids as a salvage treatment for sudden sensorineural hearing loss? A meta-analysis

Abstract: Sudden sensorineural hearing loss is typically treated with systemic steroids. The aim of this meta-analysis was to evaluate the efficacy of salvage intratympanic steroid treatment in patients who have initial treatment failure with systemic steroids. A MEDLINE literature search was performed, supported by searches of Web of Science, Biosis, and Science Direct. Articles of all languages were included. Selection of relevant publications was conducted independently by three authors. Only randomized controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 41 publications
0
50
0
5
Order By: Relevance
“…IT DEX administration causes a dose‐dependent preservation of retrocochlear auditory neurons in an NIHL mouse model . Glucocorticoids can be used as a primary initial treatment or as a salvage therapy for SSNHL, but the clinical therapeutic outcomes of IT steroid treatments are associated with the application timing, dosage, and administration protocol . Regardless, the key factor is delivery of a sufficient DEX concentration to the perilymph.…”
Section: Discussionmentioning
confidence: 99%
“…IT DEX administration causes a dose‐dependent preservation of retrocochlear auditory neurons in an NIHL mouse model . Glucocorticoids can be used as a primary initial treatment or as a salvage therapy for SSNHL, but the clinical therapeutic outcomes of IT steroid treatments are associated with the application timing, dosage, and administration protocol . Regardless, the key factor is delivery of a sufficient DEX concentration to the perilymph.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of intratympanic steroids, therefore, remains unclear. [76][77][78] Other therapies mentioned in the literature, including hyperbaric oxygen, volume expanders, vasodilators, herbal remedies, anticoagulants, and zinc, have not been studied in a rigorous fashion in any age group for sudden SNHL. Huang and Sataloff 79 reported on 7 children with autoimmune inner ear disease (AIED), with both systemic steroids and cytotoxic medications having some efficacy.…”
Section: Head Traumamentioning
confidence: 97%
“…The highest concentration and longest duration in the endolymph and perilymph was noticed after IT administration of MET compared to DEX and hydrocortisone, but resulted in increased pain and burning sensation in the ear and the throat [14] . A meta-analysis of Ng et al [16] showed better outcomes using DEX compared to MET. The concentration used in treatment is often associated with availability and approval of each country or medical center and ranged from 4 mg/mL to 24 mg/mL for DEX.…”
Section: Discussionmentioning
confidence: 99%